Electronic Structure Modulation of Non‐Noble‐Metal‐Based Catalysts for Biomass Electrooxidation Reactions. Issue 10 (9th September 2021) - Yang, Ganceng; Jiao, Yanqing; Yan, Haijing; Tian, Chungui; Fu, Honggang
Abstract : The electrochemical oxidation of biomass‐based organics has recently attracted attention due to its advantages of environmental friendliness, mild reaction conditions, high degree of conversion and selectivity, and high efficiency of hydrogen production coupled with the cathodic hydrogen evolution reaction (HER). The key to implementing the large‐scale application of the biomass electrooxidation reaction (BEOR) depends on the rational construction of efficient catalysts, as well as the structural optimization and performance improvement of the constructed catalysts. Herein, the mechanism of the BEOR is summarized, followed by a review of the current popular non‐noble‐metal electrocatalysts. Thereafter, the relationship between structure/composition and catalytic activity is systemically discussed. Furthermore, protocols for developing an effective catalyst by modulating the electronic structure, in addition to heteroatom doping, defect engineering, and heterojunction construction, are summarized and highlighted. Finally, the limitations of the current research on the construction of efficient BEOR catalysts are summarized, methods and ideas required for in‐depth research are proposed, and the goals and future development trends of BEOR research are discussed. This is expected to provide guidance for the large‐scale application of electrochemical biomass upgrading. Abstract : Recent advances in the research and development of non‐noble‐metal‐based catalysts' design to boost the performance of the biomass electrooxidation reaction are reviewed. Protocols for exploiting an effective catalyst by the modulation of the electronic structure, including heteroatom doping, defect engineering, and heterojunction construction, are summarized and highlighted.